Determinants of housing price in Hong Kong, China / Nuryusnita Hassan - Hassan, Nuryusnita (2020)
Everyone want to own at least a house as a safeguard to an individuals or family. In 2018, Hong Kong has been ranked as the most expensive residential property markets worldwide. This study is attempted to find the factors that affect housing price in Hong Kong. The independent variables selected are construction cost (CC), mortgage rate (MR), population growth (POP), income (INC), land price (LP), unemployment rate (UR), rent (RENT) and stock return (HSI). Hang Seng Stock Index (HKSI) represent the performance of Hong Kong stock market. Meanwhile for the dependent variable is Hong Kong house price index. The design of this study will comprise 76-time series data of each variable from year 2000 until 2018. The data are in quarterly basis. In findings process, there are several types of analysis were test by using Eviews11 , there are Pearson correlation coefficient and multiple regression analysis. The expected results indicate the main fundamental explanatory factors explaining Hong Kong housing price variations are household disposable income, unemployment, and land prices. The most important factor is land price. This study is useful to help the investors and buyers to decide for housing investment decision and also a guideline for government to stabilizing the demand and supply of residential property in Hong Kong.